THE HIGHER EDUCATION ADAPTABILITY TO THE DIGITAL ECONOMY - Kholiavko Nataliia; Djakona Antonina; Dubyna Maksym; Zhavoronok Artur; Lavrov Ruslan (Scientific Journal of Pedagogy and Economics, 2020)
Digitalization processes are global and performed in all spheres of economic activities. The development of the digital economy correlates with the dynamics of educational, scientific and technical, and innovative activities in the country. Higher education particularly affects the development of the digital economy because it is a system training highly qualified personnel, conducting quality research, and generating innovations. The purpose of the article is the identification of promising vectors of higher education system development under the conditions of digitalization of national economy. Section 1 of the article presents the authors’ methodological approach to assessment the impact of educational, research, and innovation components on digital economy development. The implementation of the authors’ approach covers the phased use of methods of statistical, index, cluster and system analysis. The influence of higher education on the structural components of the digital economy (educational, research, innovative ones) is grounded. The result of the study was the identification of main trends in the development of higher education under the conditions of digital economy. The problems of the development of higher education are systematized in the groups: contextual, legal, organizational and economic, financial, logistical problems, and problems of internationalization. Based on the results of the analysis, the authors conclude the necessity of development of a conceptual base for increasing the digital adaptability of the higher education system to new socio-economic conditions. Section 2 of the article describes the concept of the digital adaptability strategy of the higher education system. The concept was developed on the base of structural and functional, systemic and synergetic, and institutional approaches. The proposed concept is based on the idea of deepening the long-term partnership of universities with stakeholders within the Quadruple Helix model. In the conclusion section, the authors highlight the key priorities of the digital adaptability strategy of the higher education system.